Characteristics of Information Language Style in ISKNEWS.com Media - Muhammad Nuris Syaikhoni; Inayatul Khafidhoh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
Seeing the rapid transformation of information technology in the digital era which demands mass media to present information quickly, briefly and communicatively. Media must face challenges to maintain formal credibility that preserves emotional closeness with the audience. This research aims to analyze the characteristics of the information language style used by the digital news media platform ISKNEWS.Com and how the language style affects the effectiveness of message delivery to readers. The research method used is qualitative with a content analysis approach to published news articles. The research results show that ISKNEWS.Com consistently applies five characteristics of journalistic language namely : 1) communicative language that is familiar with the selection of words spoken by society 2) sentence specification through the use of numerical data and location that authenticity of facts 3) clarity of meaning sourced from authoritative source quotes 4) word economy with short sentence structure (S-P-K) 5) efforts to minimize the use of repeated words although still found in paragraph transitions. This linguistic strategy successfully combines formal journalism principles with everyday language, Academically, this study contributes to the development of digital communication theory, particularly in the effective use of language strategies for communicating with audiences. Theoretically, this research also contributes to the development of digital communication studies, especially regarding the use of journalistic language in local digital media. It explains how local media apply linguistic strategies to deliver information effectively, communicatively, and in accordance with the characteristics of digital audiences.